Female sexual function of overweight women with gestational diabetes mellitus - a cross-sectional study. - Meireluci Costa Ribeiro (Public Library of Science (PLoS), 2014)
Obesity and gestational diabetes mellitus (GDM) are increasing worldwide and may compromise female sexual function. We hypothesize that among GDM patients in the third trimester of pregnancy, those with excess body fat would have worse female sexual function scores than normal weight women. Our aim was to assess the sexual function of overweight compared to normal weight women with GDM. This was a cross-sectional survey involving 143 Brazilian women with GDM in the third trimester of pregnancy: 76 were overweight (pre-pregnancy body mass index-BMI≥25.0 Kg/m2) and 67 were normal weight (BMI 18.5-24.9 Kg/m2). Participants were recruited from March 2010 to April 2013 at the antenatal clinic of a single public tertiary teaching institution. The Female Sexual Function Index (FSFI) questionnaire was used to assess sexual function. Overall, 51.7% of the 143 participants were at risk for sexual dysfunction symptoms (FSFI scores ≤26); this rate was significantly higher among overweight compared to normal weight women (60.5% versus 41.8%, p = 0.038). Mean total FSFI scores were significantly lower in overweight compared to normal weight women (21.7±9.2 versus 24.9±8.0, p = 0.029). Compared to normal weight women, overweight participants had lower mean scores in desire (3.4±1.2 versus 4.0±1.4, p = 0.007) and lubrication (3.8±2.0 versus 4.5±1.6, p = 0.023). According to these results, overweight women with GDM in the third trimester of pregnancy have lower female sexual function scores than normal weight women with the same disorder.